Penguatan Pendidikan Al-Qur'an dalam Keluarga melalui Program Pengabdian kepada Masyarakat di Desa Toddopulia Kabupaten Maros - Sultan, Sultan; Damayanti, Ina; Paewai, Rusman; Jaya, Jaya (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
Strengthening Qur'anic education in the family is a strategic step to form a religious generation with noble morals. As the first and main educational environment, the family has a vital role in instilling Qur'anic values ​​from an early age. This community service activity was conducted in Toddopulia Village, Tanralili District, Maros Regency, one of the campus's partner villages. The main objective of this program is to improve the understanding and practice of Qur'anic values ​​in family life through training, coaching, and intensive mentoring for parents and community leaders. The implementation method includes socialisation, training in reading and teaching the Qur'an, and group discussions on Qur'anic education strategies in the household. The activity results showed an increase in parental awareness of the importance of their role in children's religious education and an increase in their ability to guide children to read and understand the Qur'an. This program is expected to be a sustainable model in building family spiritual resilience based on Qur'anic values.